Clinical factors associated with extreme sleep apnoea (AHI >100 events per hour) in Peruvian patients: a case-control study; a preliminary report. - Rey de Castro, Jorge (2015)
Purpose: The severity of obstructive sleep apnoea (OSA) ranges from mild or moderate to severe sleep apnoea. However, there is no information available on the clinical characteristics associated with cases involving more than 100 events per hour. This is a preliminary report and our goal was to characterise the demographics and sleep characteristics of patients with Extreme OSA and compare with patients with sleep apnoea of lesser severity. We hypothesised that patients with Extreme OSA (AHI4100) is associated with an increased comorbidities and/or risk factors. Methods: We carried out a case-control study on male patients with OSA who were seen in a private hospital in Lima, Peru between 2006 and 2012. Cases were identified if their apnoea/ hypopnea index (AHI) was higher than 100 (Extreme OSA), and four controls were selected per case: two with 15–29 AHI and two with 30–50 AHI, matched according to case diagnosis dates. We evaluated demographic, past medical history, and oxygen saturation variables Results: We identified 19 cases that were matched with 54 controls. In the multivariate model, only arterial hypertension, neck circumference, age, and over 10% in SatO2Hbr90% in total sleep time (T90) were associated with Extreme OSA. Arterial hypertension had an OR¼6.31 (CI95%: 1.71–23.23) of Extreme OSA. Each 5-cm increment in neck circumference was associated with an increase of OR¼4.34 (CI95%: 1.32–14.33), while T90410% had an OR¼19.68 (CI95%: 4.33– 89.49). Age had a marginal relevance (OR¼0.95; CI95%: 0.92–0.99) Conclusion: Our results suggest that arterial hypertension, neck circumference, and over 10% SatO2Hbr90% in total sleep time were associated with a higher probability of Extreme OSA. We recommend investigators to study this population of Extreme OSA looking for an early diagnosis and the identification of prognostic factors in comparison with moderate to severe levels.